Emotional and psychological well-being in early adolescence: psychometric properties of the Stirling children’s well-being scale in a sample of Iranian adolescents - Asgar Alimohamadi; Karim Abdolmohamadi; Mahdi Ghasemzadeh; Violeta J. Rodriguez (BMC Public Health)
Abstract Background Despite the existence of comprehensive well-being frameworks, there are notable gaps in measuring and understanding well-being in adolescents. the study examines the psychometric properties of the Sterling Children’s Well-Being Scale (SCWBS) in a large sample of Iranian adolescents. Methods This study conducted a cross-sectional investigation method on 2362 school-aged adolescents (1365 girls and 997 boys) aged 12 to 15 years, selected from a community sample in Iran (October 2023-May 2024). After a forward-backward translation, the SCWBS was adapted to the Farsi language. The SCWBS, WHO-five well-being index (WHO-5), and the Pediatric Symptom Checklist (PSC-17) were used for data collection. Assessment of reliability was conducted using internal consistency and test-retest reliability evaluations. Results The factor structure of the SCWBS was evaluated using confirmatory factor analysis (CFA), where a Cronbach’s alpha of 0.88 was obtained for the global scale, while 0.87 was obtained for the retest. According to the fit indices, the initial correlated two-factor model of SCWBS was deemed sufficient: χ2 = 646.60; df = 53; RMSEA = 0.069; CFI = 0.98; TLI = 0.98; IFI = 0.98; SRMR = 0.04. Conclusions Based on these results, the construct validity and reliability of the SCWBS are initially supported as a measurement instrument to assess the psychological well-being of Iranian adolescents.